The Day I Lost My Superpowers - Escoffier, Michael 1970-; DiGiacomo, Kris; Bedrick, Claudia Zoe (New York : Enchanted Lion Books, 2014)
When a young superhero-in-training gets hurt, she discovers that mothers have superpowers, too.
Keywords: Imagination in children -- Juvenile fiction; Play -- Juvenile fiction; Superheroes -- Juvenile fiction; Imagination -- Fiction; Play -- Fiction; Superheroes -- Fiction